Evaluation of soil chemical properties in melon cultivation land under chemical fertilizer use in Aceh Besar, Indonesia - Raichan Izzati; Ilyas Ilyas; Agra F. D. Lubis (Agrium, 2026)
This study aimed to evaluate the chemical properties of soil in melon cultivation land under chemical fertilizer use in Lam Manyang Village, Peukan Bada District, Aceh Besar, Indonesia. The research used a survey method with descriptive analysis, including soil sampling, laboratory analysis, and data processing. The observed parameters consisted of soil pH, organic carbon (C-organic), total nitrogen (N-total), available phosphorus (P-available), exchangeable potassium (K-exchangeable), and cation exchange capacity (CEC). The results showed that most soil chemical properties were classified as very low, with C-organic ranging from 0.28–0.72%, N-total from 0.05–0.15%, P-available from 0.70–3.00%, and exchangeable K from 0.08–0.19 cmol kg⁻¹, while CEC was categorized as low (10.40–13.60 cmol kg⁻¹). Soil pH values ranged from 5.23 to 6.60, indicating acidic to neutral conditions. These findings indicate that continuous reliance on chemical fertilizers without organic inputs may lead to a decline in soil chemical quality. Therefore, integrating organic amendments and balanced fertilization strategies is necessary to improve soil quality and ensure sustainable melon production.